PENGEMBANGAN BAHAN AJAR BERBASIS ENSIKLOPEDIA KEANEKARAGAMAN BUDAYA, KEARIFAN LOKAL DAN SEJARAH PADA SISWA SEKOLAH DASAR - Rahyal Piqri Nanda; Destrinelli; Muhammad Sofwan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to (1) To produce teaching material products based on an encyclopedia of cultural diversity, local wisdom and history for elementary school students. (2) To test the validity of Teaching Materials Based on the Encyclopedia of Cultural Diversity, Local Wisdom and History for Elementary School Students. (3) To determine the level of practicality of teaching materials based on the encyclopedia of cultural diversity, local wisdom and history for elementary school students This research is a type of development research using the ADDIE development model by Branch 2009 (Analyze, Design, Development, Implementation, & Evaluation). This research was conducted at SD Negeri 31 Jambi City. Research data was obtained from material validation, language validation, and media validation and data was also obtained from teacher response questionnaires and student interviews. Based on the research results, it shows that the validation of the media expert's assessment obtained an average score of 98.68% with a total of 75 being declared Very Valid/Very Appropriate, from the language expert's assessment obtaining a score of 95.45% with a total of 42 being declared Very Appropriate. and from the material expert assessment, the score was 94.23% with 49 being declared Very Eligible. Furthermore, the results of the teacher response questionnaire assessment obtained a score of 38 with a maximum of 40, so that the percentage obtained with an average score of 95% was at the Very Practical level. Based on the research results obtained, it can be concluded that the development of teaching materials based on an encyclopedia of cultural diversity, local wisdom and history for elementary school students is declared valid, very appropriate and practical.